(untitled) (GEON Journal (Management, Organizations and Business), 2020)
The covid-19 pandemic has induced a strong economic crisis, whose duration and strength are difficult to predict. Many companies in different sectors have suffered its effects. What could be done to ensure the survival of firms, not only to cope with the immediate effects of the crisis, but to overcome the difficulties of an increasingly complex and uncertain environment?. The aim of this paper is to provide some answers on this point. Thus, we examine the characteristics of this crisis, considering both the differences and the similarities with previous crises, and outlining some of the expected consequences of it. In addition, we address suggestions in the business field, both to overcome its immediate effects and to face longer-term business survival. Regarding this last point, it is proposed the achievement of two basic purposes: innovation and sustainability. And for this, a number of skills must be developed, especially three ambidexterities.